A Novel Circular RNA circITSN2 Targets the miR-218-5p/LMO7 Axis to Promote Chicken Embryonic Myoblast Proliferation and Differentiation - Shen, Xiaoxu; Wei, Yuanhang; Liu, Wei; You, Guishuang; Tang, Shuyue; Su, Zhenyu; Du, Mingxin; He, Jian; Zhao, Jing; Tian, Yongtong; Zhang, Yao; Ma, Menggen; et al. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNA (circRNA) is a class of endogenous non-coding RNAs without 5′ and 3′ ends; an increasing number of studies show that circRNA is involved in skeletal muscle development. From our previous sequencing data, the circRNAome in breast muscle of two chicken lines with a distinct rate of muscle development, which included a fast muscle growing broiler (FMGB) and a slow muscle growing layer (SMGL), we found a novel differentially expressed circRNA generated by intersectin 2 (ITSN2) gene (named circITSN2). We verified that circITSN2 is a skeletal muscle-enriched circRNA that promotes chicken primary myoblast (CPM) proliferation and differentiation. Further molecular mechanism analysis of circITSN2 in chicken myogenesis was performed, and we found circITSN2 directly targeting miR-218-5p. Besides, miR-218-5p inhibits CPM proliferation and differentiation, which is contrary to circITSN2. Commonly, circRNAs act as a miRNA sponge to alleviate the inhibition of miRNAs on mRNAs. Thus, we also identified that a downstream gene LIM domain 7 (LMO7) was inhibited by miR-218-5p, while circITSN2 could block the inhibitory effect of miR-218-5p by targeting it. Functional analysis revealed that LMO7 also accelerates CPM proliferation and differentiation, which was similar to circITSN2 but contrary to miR-218-5p. Taken together, these results suggested that circITSN2 promotes chicken embryonic skeletal muscle development via relieving the inhibition of miR-218-5p on LMO7. Our findings revealed a novel circITSN2/miR-218-5p/LMO7 axis in chicken embryonic skeletal muscle development, which expands our understanding of the complex muscle development regulatory network.